PEMBINAAN IMTAK DALAM MENINGKATKAN PERILAKU PROSOSIAL PESERTA DIDIK DI SMP NEGERI 3 PALU - -, Darmawansyah (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2021)
The study discusses coaching in improving the prosocial behavior of students at SMP Negeri 3 Palu. The research method used is descriptive qualitative research method. The research data were collected throughobservation, interview, and documentation techniques. Furthermore, it is analyzed by reducing data, presenting data and verifying data. In order to ensure the validity and credibility of the data obtained, the validity of the data is checked. Research results: (1). The form of implementing faith and piety in improving the prosocial behavior of students at SMP Negeri 3 Palu is carried out in several areas of program activities, namely; education, religion, and hygiene. (2) Supporting factors for fostering faith and piety in improving the prosocial behavior of students at SMP Negeri 3 Palu, namely the compatibility between the goals of fostering faith and piety with the goals of the school, great attention from teachers to students, and the availability of adequate facilities and infrastructure. . The inhibiting factors faced include the lack of time availability, the very diversecharacter differences of students, and the unstoppable development of technological flows